(untitled) (ІННОВАЦІЙНА ЕКОНОМІКА, 2023)
Живко М.А., Ніпіаліді О.Ю. ЦИВІЛІЗАЦІЙНІ ДЕТЕРМІНАНТИ СОЦІАЛЬНО-ЕКОНОМІЧНОЇ ПОЛЯРИЗАЦІЇ КРАЇН Мета. Аналіз і вивчення впливу цивілізаційних факторів на соціально-економічну поляризацію країн з метою виявлення головних залежностей, розкриття їх нових тенденцій та розробки рекомендацій для зменшення їх негативного впливу на національні економіки. Методика дослідження. Для досягнення поставленої мети у процесі дослідження використано наступні наукові методи: аналіз історичних даних – для визначення історичних подій та культурних процесів, які вплинули на зростання та зменшення поляризації різних регіонів та країн; культурний аналіз – для встановлення культурних аспектів різних країн (мови, релігії, традицій, ідентичності), з врахуванням їх впливу на соціально-економічну структуру та розподіл ресурсів; географічний аналіз – з метою дослідження географічних особливостей країн для визначення факторів впливу на економічно-соціальний розвиток; моделювання та статистичний аналіз – для виявлення статистичних зв’язків між різними цивілізаційними аспектами і рівнем поляризації; порівняльний аналіз – для порівняння даних між різними країнами та регіонами з метою встановлення спільних та відмінних рис, які можуть бути пов’язані з соціально-економічною поляризацією. Результати дослідження. Досліджено, як певні аспекти культури, такі як мова, релігія, традиції впливають на рівень соціально-економічної поляризації в країнах. Встановлено роль певних історичних подій у формуванні структури суспільства і рівня соціально-економічної нерівності. Розкрито, як географічні чинники впливають на розподіл багатств та можливостей країн. Встановлено загальні тенденції та подібність між різними країнами і регіонами через призму впливу цивілізаційних факторів на соціально-економічну поляризацію. Наукова новизна результатів дослідження. Проведено детальний аналіз історичних подій, які вплинули на сучасні процеси поляризації, надаючи новий рівень розуміння цього явища. Застосовано комплексний підхід, який об’єднує геополітичні, культурні та економічні аспекти життєдіяльності різних країн та регіонів, для покращення розуміння сутності соціально-економічної поляризації. Загалом, результати нашого дослідження дозволять значно розширити вплив цивілізаційних факторів на соціально-економічну поляризацію країн, що відкриває нові можливості для подальших досліджень і розвитку стратегічних векторів подолання поляризації. Практична значущість результатів дослідження. Результати дослідження допомагають поглибити знання, як культурні та історичні чинники впливають на рівень соціально-економічної поляризації. Розуміння впливу цивілізаційних факторів може допомогти країнам та міжнародним організаціям співпрацювати для розв’язання проблем поляризації та підтримки сталого розвитку. Запропоновані цивілізаційні детермінанти допомагають адаптувати освітні та культурні програми для покращення розуміння та толерантності між різними культурами та групами. Ключові слова: цивілізаційні чинники, соціально-економічна поляризація, культурні аспекти, історичні впливи, економічна нерівність, сталий розвиток, політика рівності, соціокультурна ідентичність, розподіл ресурсів. Zhyvko M.A., Nipialidi O.Yu. CIVILIZATIONAL DETERMINANTS OF SOCIAL AND ECONOMIC POLARIZATION OF COUNTRIES Purpose. The purpose of the article is to analyse and study of the influence of civilizational factors on the social and economic polarization of countries in order to identify the main dependencies, reveal their new trends and develop recommendations to reduce their negative impact on national economies. Methodology of research. The following scientific methods were used in the research process to achieve the goal: analysis of historical data – to determine historical events and cultural processes that influenced the growth and decrease of polarization of various regions and countries; cultural analysis – to establish the cultural aspects of different countries (language, religion, traditions, identity), taking into account their impact on the social and economic structure and distribution of resources; economic analysis – to assess economic indicators in order to establish the relationship between economic factors, social and economic polarization; to assess economic indicators to establish the relationship between economic factors and social and economic polarization; geographical analysis – for the purpose of researching the geographical features of countries (geographic location, climatic conditions, availability of natural resources) to determine the factors influencing economic and social development; modelling and statistical analysis – to identify statistical relationships between various aspects of civilization and the level of polarization; benchmarking – to compare data between different countries and regions in order to identify common and distinctive features that may be associated with social and economic polarization. Findings. It is studied how certain aspects of culture, such as language, religion, traditions, affect the level of social and economic polarization in countries. The role of certain historical events in shaping the structure of society and the level of social and economic inequality has been established. It has been confirmed that the influence of economic factors on social and economic polarization, such as the level of income, unemployment. It reveals how geographic factors such as location, climate, and access to resources affect the distribution of wealth and opportunity. General trends and similarities between different countries and regions regarding the influence of civilizational factors on social and economic polarization are determined. Policy recommendations have been developed to reduce social and economic polarization and promote the sustainable development of countries. Originality. A comprehensive approach was used, combining aspects of culture, history, economics and geography to better understand the essence of social and economic polarization. Cultural factors are considered in greater depth, analyzing in detail the role of language, religion, traditions and identity in the process of forming the social and economic structure. Historical analysis was used and it was determined how historical events influenced modern polarization processes, providing a new level of understanding of this phenomenon. In general, the results of our study make a significant contribution to the understanding of the influence of civilizational factors on the social and economic polarization of countries and open up new opportunities for further research and development of political strategies. Practical value. A detailed analysis of historical events that influenced modern polarization processes was carried out, providing a new level of understanding of this phenomenon. A comprehensive approach is applied, which combines geopolitical, cultural and economic aspects of the life of different countries and regions, to improve the understanding of the essence of social and economic polarization. In general, the results of our research will significantly expand the influence of civilizational factors on the social and economic polarization of countries, which opens up new opportunities for further research and development of strategic vectors for overcoming polarization. Key words: civilizational factors, social and economic polarization, cultural aspects, historical influences, economic inequality, social disparities, sustainable development, equality policy, social and cultural identity, promotion of tolerance, distribution of resources.